Risk stratification for hepatocellular cancer among patients with cirrhosis using a hepatic fat polygenic risk score - Aaron P. Thrift; Fasiha Kanwal; Yanhong Liu; Saira Khaderi; Amit G. Singal; Jorge A. Marrero; Nicole Loo; Sumeet K. Asrani; Michelle Luster; Abeer Al-Sarraj; Jing Ning; Spiridon Tsavachidis; et al. (PLoS ONE, 2023)
Background Polygenic risk scores (PRS) hold the promise to refine prognostication in hepatocellular cancer (HCC). The few available HCC PRS include germline risk variants identified among individuals of mostly European ancestry, but data are lacking on the transportability of these PRS in multiethnic U.S patients with cirrhosis from multiple etiologies. Methods We used data from 1644 patients with cirrhosis enrolled in two prospective cohort studies in the U.S. Patients were followed until HCC diagnosis, death, liver transplantation, or last study visit through June 30, 2021. The high-risk variants in PNPLA3-MBOAT7-TM6SF2-GCKR were combined in a PRS and we evaluated its association with HCC. Discriminatory accuracy was assessed using the C-statistic. Results During 4,759 person-years of follow-up, 93 patients developed HCC. Mean age was 59.8 years, 68.6% were male, 27.2% Hispanic, 25.1% non-Hispanic Black, 25.7% had NAFLD, 42.1% had heavy alcohol use, and 19.5% had active HCV. HCC risk increased by 134% per unit increase in PRS (HR = 2.30; 95% CI, 1.35–3.92). Compared to cirrhosis patients in the lowest tertile of the PRS, those in the highest tertile had 2-fold higher risk of HCC (HR = 2.05; 95% CI, 1.22–3.44). The PRS alone had modest discriminatory ability (C-statistic = 0.58; 95% CI, 0.52–0.63); however, adding PRS to a predictive model with traditional HCC risk factors had a C-statistic of 0.70 (95% CI, 0.64–0.76), increasing from 0.68 without the PRS (p = 0.0012). Conclusions Our findings suggest that PRS may enhance risk prediction for HCC in contemporary U.S. cirrhosis patients.